A multicenter study on epidemiological and clinical characteristics of 125 newborns born to women infected with COVID-19 by Turkish Neonatal Society - MEMİŞOĞLU, ASLI; ÖZDEMİR, HÜLYA (SPRINGER, 2021)
Limited data are available on pregnant women with COVID-19 and their neonates. We aimed to evaluate the epidemiological and clinical characteristics of newborns born to women infected with COVID-19. A multicenter cohort study was conducted among newborns born to mothers with COVID-19 in 34 neonatal intensive care units (NICUs) in Turkey. Pregnant women (n = 125) who had a positive RT-PCR test and their newborns were enrolled. Cesarean section, prematurity, and low-birthweight infant rates were 71.2%, 26.4%, and 12.8%, respectively. Eight of 125 mothers (6.4%) were admitted to an intensive care unit for mechanical ventilation, among whom six died (4.8%). Majority of the newborns (86.4%) were followed in isolation rooms in the NICU. Four of 120 newborns (3.3%) had a positive RT-PCR test result. Although samples taken on the first day were negative, one neonate became positive on the second day and the other two on the fifth day. Sample from deep tracheal aspirate was positive on the first day in an intubated case. Conclusion: COVID-19 in pregnant women has important impacts on perinatal and neonatal outcomes. Maternal mortality, higher rates of preterm birth and cesarean section, suspected risk of vertical transmission, and low rate of breastfeeding show that family support should be a part of the care in the NICU. Trial registration:identifier: NCT04401540 What is Known: center dot The common property of previous reports was the conclusions on maternal outcomes, rather than neonatal outcomes. center dot Published data showed similar outcomes between COVID-19 pregnant women and others. What is New: center dot Higher maternal mortality, higher rates of preterm birth and cesarean section, suspected risk of vertical transmission especially in a case with deep tracheal aspiration during the intubation, and the possible role of maternal disease severity on the outcomes are remarkable findings of this study. center dot In contrast to recommendation for breastfeeding, parents' preference to formula and expressed breast milk due to anxiety and lack of information shows that family support should be a part of the care in the NICU. Trial registration: ClinicalTrials.gov identifier: NCT04401540
Keywords: SARS-CoV-2; COVID-19; Pregnancy; Newborn; MANAGEMENT; DIAGNOSIS; CHILDREN